2016
DOI: 10.1097/ftd.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Therapeutic Drug Monitoring Practices in Intensive Care

Abstract: The performance of voriconazole therapeutic drug monitoring can still be improved although voriconazole concentrations were monitored in most patients. A multidisciplinary approach-for instance by means of antifungal stewardship-will probably be able to overcome problems encountered such as timing of sampling, incompleteness of data in clinical context, and lack of implementation of recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The 46% of non-therapeutic voriconazole levels was a little higher than reported in the majority of other studies, which ranged from 23 to 37% [ 9 , 18 , 22 25 ]. To our knowledge, only three studies reported percentages greater than 40% [ 26 28 ].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The 46% of non-therapeutic voriconazole levels was a little higher than reported in the majority of other studies, which ranged from 23 to 37% [ 9 , 18 , 22 25 ]. To our knowledge, only three studies reported percentages greater than 40% [ 26 28 ].…”
Section: Discussionmentioning
confidence: 53%
“…This study had a large percentage of drug levels that were measured early, which could be a reflection of ICU practices, as nearly half of patients in this study were critically ill. A retrospective study of voriconazole in an ICU reported that 49% of the drug levels measured for TDM were too early [ 18 ]. Given the frequency of pre-steady state TDM in real-life ICU settings, we aimed to evaluate the utility of early drug measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic monitoring of VCZ levels has been investigated due to the effects of its non-linear pharmacokinetics, especially in children [ 187 ], the elderly [ 37 ], patients in Intensive Care Units (ICU), and for hematological and inflammatory diseases [ 188 , 189 ]. The central monitoring measures have been the evaluation of CYP2C19 polymorphisms [ 190 ] and plasma drug concentration [ 189 , 191 ], in addition to the evaluation of liver function and other measures [ 192 , 193 ]. Monitoring VCZ plasma concentrations is carried out with well-standardized Liquid Chromatography coupled with Mass Spectrometry and High-Performance Liquid Chromatography methods [ 194 , 195 ].…”
Section: Voriconazolementioning
confidence: 99%
“…In practice, despite several examples of efficient dose adaptation, particularly in critically ill patients, 171 the effective rate of dose adaptation after TDM is variable 170,332 (51% or 38%), including in children. 361 A cross-sectional survey of TDM practices in Australia concluded that only 35% of clinical practices were consistent with current TDM recommendations.…”
Section: Tdm For Af Drugsmentioning
confidence: 99%